Integration and Islamisation in allied health disciplines - Zainuddin, Zainul Ibrahim (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2017)
This talk will highlight the concepts of integration and Islamisation, the two missions of International Islamic University Malaysia. These two concepts are then seen within the context of the six disciplines at the Kulliyyah of Allied Health Sciences. Similarities in the theoretical and professional domains of the six disciplines are examined to facilitate for the integration and Islamisation initiatives. The proposed approach in the integration of Islamic perspectives is aligned to the concept of Outcome Based Education (OBE). This is seen within the context of harmonising Islamic principles to a currently accepted concept in education; reducing the complexities and fatigue in addressing the integration using an educational approach that is different to that being applied to the human sciences. The discussion features the main elements in OBE in the form of Islamic programme educational objectives, Islamic programme outcomes and Islamic domain learning outcomes. The justification to use domain learning outcomes instead of course learning outcome is given. An example involving the safety domain in Medical imaging will be given to demonstrate the integration and Islamisation to Islamic perspectives or references. Currently accepted teaching and assessment methodologies can be adapted for the internalisation of the Islamic essences. Two often overlooked elements of OBE; teacher and student characteristics will be highlighted. The various terminologies that describe the Islamic teacher characteristics and the differences in student learning styles and preferences are presented. This talk contents that a holistic approach towards integration of Islamic perspectives into Allied Health Sciences can be realised.